Effect of double inversion recovery (DIR) technique, by magnetic resonance imaging, in the characterization of brain pathologies: systematic review - Pereira, M. J. (2022)
Currently, the Double Inversion Recovery (DIR) technique has an uncertain impact on clinical routine. According to some authors, the study of the brain by Magnetic Resonance with the DIR technique increases the diagnostic sensitivity for certain pathologies, however, further studies are needed to determine whether this technique should be added to the standard protocol in case of specific clinical indications. This study aimed to analyze the impact of the DIR technique appliance, in Magnetic Resonance, in the clinical routine of cerebral pathologies, through a systematic review of the literature.